Grounding Analysis Based on Different Soil Characteristics in The Distribution System - Wati, Trisna; Ramadhan, Rizky; Aji, Megi; Ramdhan, Adhitya (ELKHA : Jurnal Teknik Elektro, 2024)
This study aims to obtain the type of grounding and resistance value in the distribution system of medium voltage UP3 South Surabaya ducts. In addition, to see the magnitude of the comparative value of the results of the resistance analysis stimulates ETAP. In the South Surabaya UP3 medium voltage distribution system. PT. PLN (Persero) improves and optimizes service to all of its customers. The grounding system at PT PLN UP3 South Surabaya. The existing PLN UP3 South Surabaya must comply with PUIL regulations of 2011, and the value of land holdings must be no greater than 5 Î©. Of the 15 grounding points analyzed, there are 3 points whose grounding values do not meet the requirements of PUIL 2011, namely the grounding values are still above 5 Î©. The smallest grounding resistance value before adding the rod electrode is 1.1 Î© at the 3rd  point or BD 313 and after adding one rod and then paralleling it, the resistance value drops to 0.55 Î©. For the largest grounding resistance at the point that meets the requirements, namely 4 Î© at the 9th point or BD 653 and after adding one rod and then parallelizing it, the resistance value drops to 1.75 Î©. ETAPsimulation, the simulation results are affected by the value of x direction and the depth of the conductor. In addition, the simulation results are affected by the size of the rod. ETAP simulation results, the touch tolerable is 587.6 volts and the step tolerable is 1948.6 volts. For the largest grounding resistance at the point that meets the requirements, namely 4 Î© at the 9th point or BD 653 and after adding one rod and then parallelizing it, the resistance value drops to 1.75 Î©. ETAP simulation, the simulation results are affected by the value of x direction and the depth of the conductor. In addition, the simulation results are affected by the size of the rod. ETAP simulation results, the touch tolerable is 587.6 volts and the step tolerable is 1948.6 volts. For the largest grounding resistance at the point that meets the requirements, namely 4 Î© at the 9th point or BD 653 and after adding one rod and then parallelizing it, the resistance value drops to 1.75 Î©. ETAP simulation, the simulation results are affected by the value of x direction and the depth of the conductor. In addition, the simulation results are affected by the size of the rod. ETAP simulation results, the touch tolerable is 587.6 volts and the step tolerable is 1948.6 volts.